Controllable Triboelectric Series Using Gradient Positive and Negative Charge‐Confinement Layer with Different Particle Sizes of Mesoporous Carbon Materials. Issue 5 (24th March 2022) - Cha, Seokjun; Cho, Yujang; Kim, Jong Gyeong; Choi, Hyeongsub; Ahn, Dahye; Sun, Jingzhe; Kang, Dong‐soo; Pak, Chanho; Park, Jong‐Jin
Abstract: As a method to maximize the energy efficiency of triboelectric nanogenerators (TENGs), high‐voltage charge injection (HVCI) on the surface is a simple and effective method for increasing surface charge densities. In this study, positive and negative triboelectric series are controlled using a 3‐layer gradient charge‐confinement wherein the particle sizes of the mesoporous carbon spheres (mCSs) are sequentially arranged depending on the external surface area of the mCSs. In the gradient charge‐confinement layers of this study, the mCS with different sizes perform charge transport from the surface to a deep position during HVCI while mitigating the charge loss through charge confinement to induce the high space charge densities. Through this process, the output voltage—which is initially 15.2 V—is measured to be 600 V after HVCI, thus representing an increase of about 40 times. Further, to amplify the low output current, which is a disadvantage of triboelectric energy, two types of electrical energy—triboelectric and electromagnetic energy—are produced in single mechanical motion. As a result, the output current produced by the cylindrical TENG and electromagnetic generator is recorded as being 1300 times higher, increasing from 12.8 µA to 17.5 mA. Abstract : A 3‐layer‐gradient charge confinement layer with optimized charge transport and charge confinement is designed by synthesizing mesoporous carbon spheres with different sizes and external surface areas. After charge injection, the output voltage increases about 40 times compared to the initial value, and a high output current is achieved by additionally combining triboelectric nanogenerator and an electromagnetic generator.